2011
DOI: 10.1021/es1033487
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Plutonium Nano-Colloids by Epitaxial Distortion on Mineral Surfaces

Abstract: The subsurface migration of Pu may be enhanced by the presence of colloidal forms of Pu. Therefore, complete evaluation of the risk posed by subsurface Pu contamination needs to include a detailed physical/chemical understanding of Pu colloid formation and interactions of Pu colloids with environmentally relevant solid phases. Transmission electron microscopy (TEM) was used to characterize Pu nanocolloids and interactions of Pu nanocolloids with goethite and quartz. We report that intrinsic Pu nanocolloids gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
111
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(123 citation statements)
references
References 29 publications
12
111
0
Order By: Relevance
“…High-resolution transmission electron microscopy (HRTEM) imaging (see Fig. S6 in the supplemental material) indicated that the nanocrystalline Pu(IV)O 2 precipitates have a crystallite dimension of 2 to 3 nm, similar to those previously observed under similar solution conditions (13,42,43). The main features of the corresponding electron diffraction patterns match the face-centered cubic (fcc) Pu(IV)O 2 crystal structure (see Fig.…”
Section: Cellular Pu Sorption and Reduction Pseudomonas Sp Eps-1wsupporting
confidence: 77%
See 2 more Smart Citations
“…High-resolution transmission electron microscopy (HRTEM) imaging (see Fig. S6 in the supplemental material) indicated that the nanocrystalline Pu(IV)O 2 precipitates have a crystallite dimension of 2 to 3 nm, similar to those previously observed under similar solution conditions (13,42,43). The main features of the corresponding electron diffraction patterns match the face-centered cubic (fcc) Pu(IV)O 2 crystal structure (see Fig.…”
Section: Cellular Pu Sorption and Reduction Pseudomonas Sp Eps-1wsupporting
confidence: 77%
“…NMR analysis was performed to identify functional groups associated with the EPS. The NMR solid-state 13 C{ 1 H} CP-MAS spectrum includes distinctive peaks corresponding to carboxylic acid and acetyl functional groups likely from peptides (see Fig. S5 in the supplemental material).…”
Section: Cellular Pu Sorption and Reduction Pseudomonas Sp Eps-1wmentioning
confidence: 99%
See 1 more Smart Citation
“…This does not necessarily mean that the tetravalent ions are immobilized. Depending on the groundwater chemistry and the mineral and organic species present in the local environment, both U(IV) and Pu(IV) can be incorporated into aqueous colloids [5,27,28] or U(IV) may be con-3 verted into U(VI) by weathering [29]. In the case of bulk melt glass, the redox state of the material may impact the redox state of groundwater flowing through the test location [30,31], affecting, in turn, the solubility and transport properties of other materials.…”
Section: Introductionmentioning
confidence: 99%
“…This formulation was not observed in nano-clusters characterized by Soderholm et al (2010). In their recent work, Powell et al (2011) examined the behavior of Pu(IV) surface precipitates and colloids in the presence of goethite and quartz. Transmission electron microscopy (TEM) was used to characterize the morphology of Pu associated with these mineral phases.…”
mentioning
confidence: 99%